Does Metabolic Syndrome Effect the Perioperative Course and Costs of Patients With Hepatocellular Carcinoma Undergoing Robotic Hepatectomy? A Propensity Score-Matched Analysis. Issue 9 (September 2022) - Rayman, Shlomi; Sucandy, Iswanto; Ross, Sharona B.; Crespo, Kaitlyn; Syblis, Cameron; App, Samantha; Rosemurgy, Alexander
Background: This study was undertaken to examine the postoperative outcomes, costs, and survival after robotic hepatectomy for hepatocellular carcinoma (HCC) in patients with or without metabolic syndrome. Methods: Following IRB approval, we prospectively followed 56 patients undergoing robotic hepatectomy for HCC from 2016-2020. Patients with metabolic syndrome were compared to patients without metabolic syndrome regarding postoperative clinical outcomes, costs, and survival. Propensity score matching of a 1:1 ratio matched patients with and without metabolic syndrome according to 6 variables. Results: 17 patients were matched to each arm. Mean age was 64 ± 14.0 years and 30 patients (88%) had operations that were classified as advanced (IWATE 7-9) or expert (IWATE 10-12). There were no differences between patients with metabolic syndrome versus patients without metabolic syndrome in terms of operative duration (306 [301 ± 76.2] vs 239 [260 ± 116.9] minutes; P = 0.23), estimated blood loss (300 [321 ± 195.5] vs 200 [214 ± 151.4] ml; P = 0.08), conversion to "open" operation (1 [6%] vs 1 [6%]; p = 1.00), tumor size (5 [5 ± 3.0] vs 3 [4 ± 2.2] cm; P = 0.28), postoperative complications with Clavien-Dindo Score (≥III) (0 vs 1; P = 1.00), in-hospital mortality (0 [0%] vs 1 [6%]; P = 1.00), length of stay (5 [5 ± 1.7] vs 4 [5 ± 4.4] days; P = 1.00), and 30-day readmissions (1 [6%] vs 1 [6%]; P = 1.00). There were no differences in overall costs and profit. There was no difference in 1-year, 2-year, and 3- year overall survival in patients with or without metabolic syndrome after robotic HCC resection (84% vs 77%, 84% vs 61%, and 45% vs 61%, P = 0.42). Conclusion: For patients with and without metabolic syndrome, robotic advanced/expert hepatectomy for HCC resulted in similar intra-operative metrics, postoperative outcomes, costs, and survival.